National policy for integration of ICT: a comparative study between Brazil and Spain - José GOMES DA SILVA; Maria NEIDE SOBRAL (Ediciones Universidad de Salamanca, 2018)
This article aims to present the results of a comparative study of national educative policies for integration of information and communication technologies (ICT) used in basic education schools in Brazil and Spain. In general terms, this article intends to examine possible convergences and divergences in objectives presented by these policies. The time frame was between 1997 and 2010, when these policies and the launch of new transnational policies for ICT integration began. The research has a qualitative approach and a descriptive and documentary procedure, through the comparative study method. The sources were laws, resolutions, regulations, decrees, regulatory guidelines, official informs, official communications and technical reports. So, on the whole, we ascertained that these policies seek an educational quality, aligned by the market logic, with constitutive elements of the recommendations of international organisations, and they are directed to the technological development and economic growth, thus legitimizing the hegemonic discourse of globalization.